Embracing digital generation: Analysis of Hanan Attaki's podcast media as a da'wah medium - Divya Zahrani Khaerunnisa; Lutfiah Khoirunnisa Azzahro; Mochamad Rizky Tri Wardana; Nazwa Fauziah; Muhammad Wildan Alginani; Achmad Faqihuddin (Jurnal Al-Hikmah, 2024)
This study discusses the struggle to reach the digital generation as a target of da'wah in the Social Media Era, focusing on analyzing Hanan Attaki's Podcast media as a media for da'wah. Given that the development of technology today leads humans to practice their lives online, including religious practices, especially da'wah activism, new methods are needed so that da'wah can run optimally. This article specifically aims to analyze the role of Podcast media in delivering da'wah messages to the digital generation. This article will explain the influence that can be gained by using podcasts as a da'wah media, their advantages and disadvantages, and their effectiveness in delivering the da'wah message itself. A qualitative approach with literature study and content analysis methods is used to analyze and explore in depth how podcasts, as a medium, can be used to reach an increasingly digitally connected audience. The research findings show that Podcastscan is an effective digital da'wah media because it can help audiences listen to da'wah more easily and flexibly. The practical implication of this research is the importance of utilizing media as an effective means of delivering da'wah in an effort to reach the digital generation.